STRATEGI ONLINE UNTUK PRODUK BUKU BACK LIST PADA TOKO BUKU ONLINE BOOKOOPEDIA.COM - , Retno Suffatni, SP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to identify the avaibility of back list in marketplace and its strategy to improve its access. The key factor for books to be found and well sold is the aspect of their avaibility in market. Ideally, the books must be placed in a strategic shelf. Therefore, costumers not only get enough access to learn new imprints, but also old publications that published several months ago. In a competitive shelves in a brick and mortar bookstore this condition is rarely to be found. Publishing industry characterictics that emphasize on the up to date and new trends as well as focused on outstanding promotion for best seller have made the back list as forgotten phenomenon. This research was conducted in Bookoopedia.com online bookstore. The primary data was obtained from direct and indirect interview. The secondary data was collected from catalog list, record sales, top selling book list, year of publication, and publisher. To analyze the data obtained, the Long Tail theory approach was used. The results showed that Bookoopedia.com provides catalog and virtual inventory. Therefor, it can display all published books especially back list. By using internet as the main media for marketing and selling, the problem of limited display space can be minimized. Opportunity loss decrease and back list book is identified. Bookoopediaâs strategy to enhance back list access is by providing many and various choices of imprints, decreasing opportunity loss using virtual catalog dan virtual inventory, and creating blog to interact with customers, testimony, books review, and book recomendation.